Understanding creative design processes by integrating sketching and CAD modelling design environments: a preliminary protocol result from architectural designers - Shih, Yi Teng; Sher, William D.; Taylor, Mark (Aga Khan Documentation Center, 2015)
This paper presents the results of a preliminary protocol study of the cognitive behaviour of architectural designers during the design process. The aim is to better understand the similarities and differences in cognitive behaviour using Sequential Mixed Media (SMM) and Alternative Mixed Media (AMM) approaches, and how switching between media may impact on design processes. Two participants with at least one-year’s professional design experience and a Bachelor of Design degree, and competence in both sketching and computer-aid design (CAD) modelling participated in the study. Video recordings of participants working on different projects were coded using the Function-Behaviour-Structure (FBS) coding scheme. Participants were also interviewed and their explanations about their switching behaviours were categorised into three types: S→C, S/C↹R and C→S. Preliminary results indicate that switching between media may influence how designers identify problems and develop solutions. In particular, two design issues were identified.  These relate to the FBS coding scheme, where structure (S) and behaviour derived from structure (Bs), change to documentation (D) after switching from sketching to CAD modelling (S→C). These switches make it possible for designers to integrate both approaches into one design medium and facilitate their design processes in AMM design environments.